Capsaicin attenuates liver fibrosis by targeting Notch signaling to inhibit TNF-α secretion from M1 macrophages. (1st November 2020) - Sheng, Jianping; Zhang, Baohang; Chen, Yongfeng; Yu, Fuxiang
Abstract: Background: Capsaicin is a chili pepper extract with multiple therapeutic properties including anti-liver fibrosis. However, the paucity of its underlying mechanisms limited its widely clinical application. Methods: In the present study, carbon tetrachloride (CCl4 ) was used to induce liver fibrosis in mice, and transforming growth factorβ1 (TGFβ1) was used to mimic liver fibrosis in vitro . Flow cytometry was conducted to determine the expression of CD80. The inflammatory factors level was examined by ELISA, and gene expression was detected by real-time PCR and western blot. Results: Here, we show that capsaicin attenuates liver fibrosis progression by mediating macrophage inflammatory response. Capsaicin inhibited M1 polarization of macrophage by regulating Notch signaling leading to the reduced secretion of inflammatory cytokine TNF-α that correspondingly attenuates myofibroblasts regeneration and fibrosis formation of hepatocyte stellate cells (HSCs). Conclusion: Taken together, capsaicin alleviates liver fibrosis by inactivation of Notch signaling and further inhibiting TNF-α secretion from M1 macrophage. Targeting TNF-α or Notch signaling in macrophage represents a promising strategy to combat liver fibrosis.